Test engagement and rapid guessing: Evidence from a large-scale state assessment - Svetina Valdivia, Dubravka; Rutkowski, Leslie; Rutkowski, David; Canbolat, Yusuf; Underhill, Stephanie (Frontiers in Education, 2023)
A recent increase in studies related to testing behavior reignited the decades long conversation regarding score validity from assessments that have minimal stakes for students but which may have high stakes for schools or educational systems as a whole. Using data from a large-scale state assessment (with over 80 thousand students per grade), we examined rapid-guessing behavior via normative threshold (NT) approaches. We found that the response time effort (RTE) was .991 and .980 in grade 3 and grade 8, respectively, based on the maximum threshold of 10% (NT10). Similar rates were found based on methods that used 20% and 30%. Percentages of RTEs below .90, which indicated meaningful disengagement, were smaller in grade 3 than grade 8 in all normative threshold approaches. Overall, our results suggested that students had high levels of engagement on the assessment, although descriptive differences were found across various demographic subgroups.